2014
DOI: 10.1111/socf.12123
|View full text |Cite
|
Sign up to set email alerts
|

Humanitarian Crisis as Everyday Life

Abstract: Contemporary scholarship understates the resilience of everyday life in humanitarian crisis. Disaster may seem like a fleeting moment-colloquially, we say "the world stood still" or "everything changed in a blink"-but in the Buduburam Refugee Camp, a predominately Liberian refugee camp in Ghana, people experienced calamitous tragedy accumulated over years of daily activities. Though they remained politically and economically "out of place," residents constructed buildings and other ordinary material objects to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…As they explained, protracted displacement had become protracted uncertainty (Brun, 2015). There is an existing and growing body of work on how refugees construct their lives in such uncertainty, in protracted displacement, and in everyday emergency (Dryden-Peterson, 2006;Grabska, 2006;Holzer, 2014;Brun, 2015;Horst and Grabska, 2015). As yet, however, little of this work has considered the role of household-level hosting arrangements within refugees' experience of the present and their work for the future [though see (Fiddian-Qasmiyeh, 2016;Yassine et al, 2021)].…”
Section: Care Dynamics In Protracted Displacementmentioning
confidence: 99%
See 1 more Smart Citation
“…As they explained, protracted displacement had become protracted uncertainty (Brun, 2015). There is an existing and growing body of work on how refugees construct their lives in such uncertainty, in protracted displacement, and in everyday emergency (Dryden-Peterson, 2006;Grabska, 2006;Holzer, 2014;Brun, 2015;Horst and Grabska, 2015). As yet, however, little of this work has considered the role of household-level hosting arrangements within refugees' experience of the present and their work for the future [though see (Fiddian-Qasmiyeh, 2016;Yassine et al, 2021)].…”
Section: Care Dynamics In Protracted Displacementmentioning
confidence: 99%
“…For the men I worked with, and for many refugees, emergency is not a one-time short event, but something that repeats and extends. Holzer (2014) has spoken about the maintenance of life through emergency, it is not some brief blip, but something that people persist through. Hosting is one way that refugees engage with this, and in doing so in what Feldman (2012) calls a politics of living, of surviving, of claiming.…”
Section: Care Dynamics In Protracted Displacementmentioning
confidence: 99%
“…Existing research on refugee resettlement often downplays the wider everyday life in which these decisions are made by instead focusing on the legal dynamics of determining refugee status (Kagan, 2002(Kagan, , 2006(Kagan, , 2010, the institutional structures of opportunity in resettlement (Nawyn, 2006(Nawyn, , 2010, and experiences of integration and acquiring of citizenship after resettlement decisions (Bloemraad, 2006;Ong, 2003). However, law becomes part of everyday life in humanitarian contexts (Ewick & Silbey, 1998;Holzer, 2013Holzer, , 2014Jacobs & Kyamusugulwa, 2018;Merry, 2006). Resettlement processes are one of the main ways law enters everyday life in refugee camps (Warren, 2023).…”
Section: Migration Everyday Life and Humanitarianismmentioning
confidence: 99%
“…But that was not the extent of their grievances. During my fieldwork with displaced Timbuktians in 2013, many revealed that their crisis of displacement was too profound to be captured by the concepts commonly used to discuss displacement, including material hardship and fear of violent persecution (Holzer ; Malkki ). To understand forced displacement, therefore, one must not only examine the dominant themes surrounding IDPs and refugees but also analyze local conceptual frameworks through which they organize their experiences (Malkki ; Nordstrom , ).…”
mentioning
confidence: 99%